Minecraft redstone essentials and must-do projects - Dusmann, Cori (Peachpit Press, 2015)
"This video explores exactly what redstone is, how we can use it, and the tools that are part of working with redstone. We'll look at some projects, breaking them down step by step, so that you can see redstone in action. Soon you'll be using redstone with ease! "--Resource description page.